Rootstock Priming with Shikimic Acid and Streptomyces griseus for Growth, Productivity, Physio-Biochemical, and Anatomical Characterisation of Tomato Grown under Cold Stress - Eman G. Sayed; Abdel Wahab M. Mahmoud; Ahmed Abdel-Wahab; Reham M. El-bahbohy; Samah N. Azoz (Plants, 2022)
With this research, we aimed to determine the impact of grafting and rootstock seed treated with Streptomyces griseus (MT210913) (S. griseus) or shikimic acid (SA) at a 60 ppm concentration on tomato (Solanum lycopersicum L.) production grown under low-temperature conditions. Two open-field trials were performed during both winter seasons of 2020 and 2021 at the Experimental Farm, Faculty of Agriculture, Cairo University, Giza, Egypt. A tomato cultivar (Peto 86) was used as a scion and two tomato phenotypes were employed as rootstocks (Solanum cheesmaniae L. (line LA 524) and GS hybrid), as well as self-grafted as a control. Effects of sub-optimal temperature on vegetative growth, yield, and fruit quality were tested. The results indicate that, under cold stress, rootstock seed priming, especially with S. griseus, enhanced plant growth, total yield, and fruit quality properties. GS hybrid rootstock was more effective than that of S. cheesmaniae rootstock in terms of mitigating the negative effect of cold stress. GS hybrid, inoculated with S. griseus, increased the total yield per plant by 10.5% and 5.7% in the first and second seasons, respectively. Higher levels of GA3 and mineral content were noticed in leaves that were grafted and treated with S. griseus compared to the control treatment. Additionally, the great enhancing effects of all anatomical features of tomato plants were recorded with GS hybrid rootstock, inoculated by S. griseus. These results prove that grafting on GS hybrid rootstock treated with S. griseus is a potential choice to alleviate the cold stress of commercial tomato varieties.